Kemampuan Tawar Pekerja Seks Komersial dalam Penggunaan Kondom untuk Mencegah Penularan HIV/AIDS di Jalan Lintas Sumatera Kabupaten Langkat Propinsi Sumatera Utara - Kenderwis Ida Yustina (Fakultas Kedokteran Universitas Gadjah Mada, 2010)
Background: Commercial sex workers is one of high risk group in spreading of HIV/AIDS. In Langkat District, till October 2007 there were 7 cases AIDS reported from prostitutes.Objectives: The purpose of the study was to analyze the influence of their predisposing factors (knowledge and attitude), enabling factors (complexity of condom, availability of condom, customer’s comfort) and reinforcing factors (family, Non-Government Organization/NGO, health workers, opinion leader) on commercial sex workers bargaining power in using condom.Methods: This was an explanatory survey which was conducted in Langkat District towards 104 commercial sex workers in 2008. Data collected by interview using questionaire; were processed by using multiple regressions.Result and Conclusion: The result of study showed that 70,2% of the commercial sex workers bargaining power in asking their customers to use condom were in bad category. The result of multiple regression analysis showed that 85,6% of the commercial sex workers bargaining power to ask their customers to use condom can be explained by the knowledge and attitude of the commercial sex workers, complexity of condom, customer’s comfort, and Non Governmental Organization.Keywords: bargaining power, commercial sex workers, condom